Further records and new data on the occurrence of Martyniaceae in Tunisia and North Africa - El Mokni, Ridha (Hacquetia, 2021)
Proboscidea louisianica (Miller) Thell. (Martyniaceae) is newly reported for the flora of Tunisia and North Africa as a naturalised alien. Extensive field investigations in northern Tunisia allowed the discovery of three populations of P. louisianica (Miller) Thell. consisting of 18 individuals were found at the edges of “Oued Beja” and at roadside within an irrigated land in Nabeul region, where plant specimens were in flowers and fruits. Moreover, further sites were recorded for the other member of the family Martyniaceae (Ibicella lutea (Lindl.) Van Eselt.), already reported and known in Tunisia and Algeria within North Africa. Additional information for both species on their current distribution areas and their habits are provided. Details of their morphological and distinguish features are illustrated.